Successful Management of a Pancreatic Abscess in a Dog with Juvenile Diabetes Mellitus Through Ultrasound-Guided Drainage and Medical Therapy - Alexandra Daravigka; Stefanos Ninis; Panagiotis Bourdekas; Alexandros O. Konstantinidis; Argyrios Ginoudis; Katerina K. Adamama-Moraitou; Maria Lyraki; Nektarios Soubasis (Veterinary Sciences)
A five-month-old female mixed-breed dog presented with a two-week history of polyuria, polydipsia, and vomiting. Clinical examination revealed poor body condition, growth retardation, pale oral mucous membranes, weak pulse, and prolonged capillary refill time. Laboratory findings included neutrophilic leukocytosis with a regenerative left shift, fasting hyperglycemia, elevated fructosamine, glycated hemoglobin, and β-hydroxybutyrate concentrations, while the acid–base balance remained normal. Canine-specific pancreatic lipase and trypsin-like immunoreactivity concentrations ruled out an underlying pancreatitis or exocrine pancreatic insufficiency, respectively. Urinalysis showed glycosuria and ketonuria. Supportive care included antibiotics and regular insulin administration. Abdominal ultrasonography identified a pancreatic cavity with a thick wall and mixed echogenic fluid. Ultrasound-guided drainage was performed without complications. Cytology confirmed a pancreatic abscess with pyogranulomatous inflammation, though the culture results were negative. The dog was discharged with intermediate-acting lente insulin. Follow-up ultrasonographic evaluations at 7, 14, and 21 days and 5 months post-drainage showed no recurrence. The diabetes remained well-controlled one year post-discharge. This case report describes the successful management of a dog with juvenile diabetes mellitus complicated by a pancreatic abscess, highlighting the effectiveness of percutaneous ultrasound-guided drainage combined with medical therapy.